Notes on the concept of representativeness (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Considering the emerging of a new movement that advocates for self-representation in the arts, this article brings some reflections on the ethical, aesthetic, political and social implications that permeate the representation of minority social groups in contemporary theater. Starting from the construction of an understanding of the concept of representativeness within the Brazilian performing arts field and an analysis of some ways it can operate in and out of theater, the article also presents proposals for artists who aim to create under a representative, plural and emancipatory perspective.
Keywords: Representativeness.; Representation; Ethics; Contemporary scene; Diversity